2008
DOI: 10.1080/10790268.2008.11760724
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles of Persons With Paraplegia and Tetraplegia: Sex Differences

Abstract: Background/Objective: To examine the lipoprotein profiles of men and women with paraplegia and tetraplegia. Impairment of the sympathetic nervous system (dependent on the level of injury) and the extent of physical capacity and activity were correlated with the lipid profile in men with spinal cord injury (SCI). Sex-related differences of the lipoprotein profiles could be found in nondisabled and premenopausal women with SCI mainly because of the different effects of sexual hormones. Methods: Lipoprotein profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
3
5
0
Order By: Relevance
“…Previous reports in TSCI have implicated a greater number of lipid abnormalities than those with PSCI, 10 while others have reported elevated TC, LDLC, and HDLC profiles and a lower TC:HDLC ratio in individuals with PSCI than those with TSCI. 4,8,[43][44][45] We have demonstrated similar results showing elevated TC, LDLC, and HDLC, but a lower TC/HDLC ratio. The relatively elevated HDLC profiles observed in the PSCI group may stem from a larger LBM percentage and better aerobic fitness, which has been implicated in favorable HDLC profiles in PSCI versus TSCI.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous reports in TSCI have implicated a greater number of lipid abnormalities than those with PSCI, 10 while others have reported elevated TC, LDLC, and HDLC profiles and a lower TC:HDLC ratio in individuals with PSCI than those with TSCI. 4,8,[43][44][45] We have demonstrated similar results showing elevated TC, LDLC, and HDLC, but a lower TC/HDLC ratio. The relatively elevated HDLC profiles observed in the PSCI group may stem from a larger LBM percentage and better aerobic fitness, which has been implicated in favorable HDLC profiles in PSCI versus TSCI.…”
Section: Discussionsupporting
confidence: 74%
“…44,46,47 With reference to TG, greater levels of inactivity, such as that reported with higher levels of SCI, have been reported to reduce lipoprotein lipase resulting in elevated levels of circulating TG. 43 This observation could account for the elevated levels of TG in the TSCI who have less LBM available for leisure and physical activity versus PSCI. Higher levels of TG have also been previously reported by Schmid et al 43 and Gibson et al 23 Moreover, elevated catecholamine levels have been reported in PSCI due to greater activity of the SNS, 43 which may increase lipolysis and the eventual production of LDLC, thus accounting for the overall increase in TC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was a difference in the prevalence of low HDL-C and high LDL-C between genders which may have been a result of different sex hormones that influence blood lipid profiles [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 There are also studies reporting that the higher serum catecholamine levels in patients with paraplegia than patients with tetraplegia due to the increased sympathetic activity in patients with paraplegia lead to high serum LDL-c levels. 25 Despite some studies reporting a relationship between the lesion level and serum lipid levels, no such relationship was found in many studies 16,26,27 and also in a collective work in 2008. 15 HDL-c levels in patients with motor complete SCI were significantly lower than patients with motor incomplete SCI in our study and we found no relationship between other serum lipid levels and lesion grade.…”
Section: Discussionmentioning
confidence: 99%